On Nichols algebras of infinite rank with finite Gelfand-Kirillov dimension - Andruskiewitsch, Nicolas (2020)
We classify infinite-dimensional decomposable braided vector spaces arising from abelian groups whose components are either points or blocks such that the corresponding Nichols algebras have finite Gelfand-Kirillov dimension. In particular we exhibit examples where the Gelfand-Kirillov dimension attains any natural number greater than one.